Definition of the Bleeding Tendency in Factor XI-Deficient Kindreds–A Clinical and Laboratory Study - Bolton-Maggs, P H B; Patterson, D A; Wensley, R T; Tuddenham, E G D (Thrombosis and Haemostasis, 1995)
Individuals with severe factor XI deficiency are prone to excessive bleeding after injury or surgery, but the existence of a haemorrhagic tendency in partial factor XI deficiency is controversial. In this study, 172 members of 30 kindreds (20 non-Jewish) transmitting factor XI deficiency in North West England were interviewed and a bleeding history questionnaire completed. Blood was taken for coagulation assays. The questionnaires were categorised independently by two assessors to determine presence or absence of a bleeding tendency, in the absence of information about the factor XI level or family history. Analysis shows that 48% of heterozygotes have a bleeding tendency. Eighteen (60%) families came to attention because of bleeding problems in heterozygotes. Comparison of histories between partially deficient and non-deficient individuals demonstrated a higher incidence of menstrual problems, an increase in significant bruising, and an increased likelihood of excessive bleeding after tonsillectomy and dental extractions.The incidence of von Willebrand’s disease was not increased, but individuals with heterozygous factor XI deficiency who were bleeders tended to have lower levels of factor VIIIc and von Willebrand factor, and were more commonly of blood group 0. These features may contribute to the bleeding tendency. There was no evidence of alteration in factor VII activity (as defined by the ratio of activity to antigen) between the bleeders and non-bleeders.This is convincing evidence for abnormal bleeding in factor XI deficiency which is not confined to severely deficient patients.